Optimization of ultrasonic-assisted extraction of total flavonoids from Zanthoxylum bungeanum residue by response surface methodology and evaluation of its algicidal properties - Cheng, Jie; Tan, Long; Wang, Yucai; Gao, Mengwei; Liu, Feifei; Wang, Qi; Xu, Chengshuai; Zhang, Chaobo; Xu, Wei; Hou, Yuyong; Jiang, Tong; Zhao, Lei (Frontiers in Microbiology, 2025)
Zanthoxylum bungeanum residue has attracted increasing attention owing to its antibacterial effect, which presents potential as novel antimicrobial agents for the management of algal blooms. In this study, the ability of Z. bungeanum residue extract to control algal blooms has been firstly verified. Then, the response surface methodology was employed to optimize flavonoids yield, the primary antimicrobial component in extract, and the underlying photosynthetic inhibition mechanisms of extract on Tetrodesmus obliquus was investigated. Results showed that the highest yield of total flavonoids was increased to 4.08% when the extraction conditions were a liquid-to-solid ratio of 10:1, ethanol concentration of 60%, extraction temperature of 80°C, and extraction time of 30 min. Meanwhile, treatment with Z. bungeanum residue extract at doses of 40.0 mg/L significantly decreased the Fv/Fm and PIabs values of T. obliquus by 24.36 and 88.87% at 50 h, respectively. The added extract induced damage at multiple levels of physiological and biochemical processes in algal cells, including reduced electron transport capability, disrupted energy transfer in photosystem II, disruption of OEC structure, and altered energy distribution in PSII reaction center. To our knowledge, this study was the first verification of Z. bungeanum residue’s algicidal potential, and these findings in our study contribute to a deeper understanding of the allelopathic mechanisms of Z. bungeanum residue extract and offer valuable insights for the management of algal blooms.